A novel microalgal biofilm reactor using walnut shell as substratum for microalgae biofilm cultivation and lipid accumulation. (September 2021) - Zou, Xiaotong; Xu, Kaiwei; Chang, Wenjuan; Qu, Yanhui; Li, Yanpeng
Abstract: Microalgae are a potential candidate for biofuels, but the high cost and low biomass yield hinder the scale-up application of microalgae. In this study, a novel walnut shell based self-permeating biofilm reactor (WSPBR) was proposed for cultivation of Chlorella vulgaris ( C. vulgaris) and Scenedesmus obliquus ( S. obliquus ). Major influencing factors such as walnut shell size, light intensity and CO2 concentration were studied in detail. The results showed that CO2 can enhance the storage of metabolic products in microalgal cells. Thermodynamics analysis indicated that C. vulgaris and S. obliquus were likely to adhere on the surface of walnut shells. S. obliquus and C. vulgaris biomass reached the maximum values of 97.43 and 70.49 g m −2, respectively, corresponding to the walnut shell size of 0.8–1.2 mm, light intensity of 150 μmol m −2 s −1 and CO2 concentration of 2%. The lipid contents of these microalgal cells were 34.32% and 28.94%, respectively. These results indicated that WSPBR was an efficient system for microalgae cultivation as feedstock for biofuels. Graphical abstract: Image 1 Highlight: A self-permeating biofilm reactor based on walnut shell was proposed. Walnut shells were used as substratum to support microalgae biofilm. Cultivation in this novel reactor enhanced biomass production and lipid content. Thermodynamics analysis was applied to evaluate the biofilm attachment process.